Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1083/jcb.201708168
|View full text |Cite
|
Sign up to set email alerts
|

Rapid induction of p62 and GABARAPL1 upon proteasome inhibition promotes survival before autophagy activation

Abstract: Cells are thought to adapt to proteasome inhibition by using alternative pathways for degradation such as autophagy. Sha et al. now report that cells rapidly induce GABARAPL1 and p62 upon proteasome inhibition, but this promotes cell survival by sequestering ubiquitinated and sumoylated proteins long before the cells induce other Atg genes and activate autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
75
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 74 publications
13
75
0
1
Order By: Relevance
“…Following substrate ubiquitylation, p62 (or other adaptors) binds to poly-ubiquitinated proteins via the UBA domain. Increasing evidence revealed the crosstalk and reciprocal regulatory mechanisms between the two pathways, by which useless materials that accumulate following inhibition of one degradative system could be cleared by the other system [18][19][20]. We previously revealed starvation induced nuclear export of deacetylated LC3, which became the resource of membrane-associated LC3 [3,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following substrate ubiquitylation, p62 (or other adaptors) binds to poly-ubiquitinated proteins via the UBA domain. Increasing evidence revealed the crosstalk and reciprocal regulatory mechanisms between the two pathways, by which useless materials that accumulate following inhibition of one degradative system could be cleared by the other system [18][19][20]. We previously revealed starvation induced nuclear export of deacetylated LC3, which became the resource of membrane-associated LC3 [3,17].…”
Section: Discussionmentioning
confidence: 99%
“…Despite of the different mechanisms, ubiquitylation is the degradation signal by both systems. Increasing evidence revealed the crosstalk and reciprocal regulatory mechanisms between the two pathways, by which useless materials that accumulate following inhibition of one degradative system could be cleared by the other system [18][19][20]. The proteasome-mediated degradation of LC3 is one mechanism of autophagy regulation by proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…A study using fruit flies showed that HDAC6 mediated autophagic activation by proteasome inhibition; 41 however, PSMI does not appear to upregulate HDAC6 in mammalian cells. 45 Several transcription factors such as p53, 46,47 Nrf2, 48 and NFκB, 49,50 have been shown to regulate the transcription of a subset of autophagy genes.…”
Section: Proteasome Malfunction Activates Tfebmentioning
confidence: 99%
“…Babu et al, 2005). However, it was suggested that the condensates function to sequester ubiquitylated proteins in neuroblastoma cells (Sha et al, 2018). How substrate sequestration and autophagosome formation are coordinated is an important open question (Fig.…”
Section: P62-ubiquitin Condensates As Substrates For Autophagymentioning
confidence: 99%